The altering cellular components and function in tumor microenvironment during remissive and relapsed stages of anti-CD19 CAR T-cell treated lymphoma mice - Zhao, Kai; Ren, Chunxiao; Tang, Donghai; Zhao, Li; Chen, Xianxian; Wang, Ying; Xu, Kailin (Frontiers in immunology, 2023)
Anti-CD19 chimeric antigen receptor (CAR) T cells represent a highly promising strategy for B-cell malignancies. Despite the inspiring initial achievement, remission in a notable fraction of subjects is short-lived, and relapse remains a major challenge. Tumor microenvironment (TME) was proved to be aroused by CAR T cells; however, little is known about the dynamic characteristics of cellular components in TME especially during the different phases of disease after anti-CD19 CAR T-cell treatment. We took advantage of an immunocompetent model receiving syngeneic A20 lymphoma cells to dissect the changes in TME with or without CAR T-cell injection. We found that anti-CD19 CAR T-cell treatment attenuated the symptoms of lymphoma and significantly prolonged mice survival through eradicating systemic CD19 + cells. Increased myeloid subsets, including CD11c + DCs and F4/80 + macrophages with higher MHC II and CD80 expression in bone marrow, spleen, and liver, were detected when mice reached remission after anti-CD19 CAR T treatment. Compared to mice without anti-CD19 CAR T administration, intrinsic T cells were triggered to produce more IFN-γ and TNF-α. However, some lymphoma mice relapsed by day 42 after therapy, which coincided with CAR T-cell recession, decreased myeloid cell activation and increased Treg cells. Elevated intrinsic T cells with high PD-1 and TIGIT exhaust signatures and attenuated cytotoxicity in TME were associated with the late-stage relapse of CAR T-cell treatment. In summary, the cellular compositions of TME as allies of CAR T cells may contribute to the anti-tumor efficacy at the initial stage, whereas anti-CD19 CAR T-cell disappearance and host response immunosuppression may work together to cause lymphoma relapse after an initial, near-complete elimination phase.